Transforming science classrooms through evidence-based teaching practices - Solibek Yunus oglu Mirimov (Science and Education, 2025)
The transformation of science classrooms through evidence-based teaching practices has become increasingly essential in modern education. Traditional instruction, often reliant on lectures and rote memorization, fails to engage students fully or foster deep understanding of scientific concepts. Evidence-based teaching integrates instructional strategies validated through empirical research, ensuring that classroom practices effectively promote learning, critical thinking, and problem-solving. This article examines the theoretical foundations, practical applications, and outcomes of evidence-based approaches in science education, including active learning, formative assessment, scaffolding, differentiation, and technology integration. It highlights the role of metacognition and collaborative learning in enhancing student engagement and cognitive development. Challenges associated with implementing research-informed practices, such as resource limitations and teacher readiness, are also discussed. The findings suggest that evidence-based teaching not only improves academic performance but also cultivates scientific literacy, critical reasoning, and lifelong learning skills. By embedding research-informed practices in science instruction, educators can create dynamic, student-centered learning environments that prepare learners to navigate complex scientific and real-world challenges effectively.